Creating competitive organizational strategy using the funnel method - Stefanovska, Lidija; Solunčevski, Mande (Serbian Journal of Management, 2015)
In the highly competitive environment of the 21st century, organizations must be able to effectively change through the application of effective strategies, quickly and in a way that the competitors will be unable to imitate. Therefore, the essential question in any organization is how to achieve and maintain competitive advantage. In this regard, strategic leaders should first logically consider what will bring a substantial advantage to the organization in a long-term, and then start with the process of creating the strategy. To achieve this, researchers in the field of managerial issues offer a concept of continuous process that begins by looking at the customers pattern, through defining the competitive environment and the place of business in it and finally categorizing several strategic business conditions, as a precondition for election and creation of a competitive strategy. This process can be presented as the “funnel for selection of competitive strategy”, in whose widest part we can put the customer matrix, in the middle part we can place definitions of the business outlook of the business and the position of the organization in those perspectives. In order to implement the "Funnel method" of strategic planning teams we need accurate, timely and relevant information based on which we can bring appropriate organizational strategy. The subject of this paper is displaying the Funnel method for selection of the competitive strategy, and presentation of the situation in some of the organizations in the Pelagonija region, related to the way and the information used to create organizational strategies through the Funnel method.